2020
DOI: 10.3390/nano10091802
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Dilution of Noble NPs Bulk Dispersions: Modeling Instability due to Dissolution by AF4 and Stablishing Considerations for Plasmonic Assays

Abstract: Among different nanomaterials, gold and silver nanoparticles (AuNPs and AgNPs) have become useful tools for a wide variety of applications in general, and particularly for plasmonic assays. Particle size and stability analysis are key elements for their practical applications since the NPs properties depend on these parameters. Hence, in the present work, asymmetrical flow field flow fractionation (AF4) coupled to UV-Vis and dynamic light scattering (DLS) detectors in series, has been evaluated for stability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These changes depend on the kinetics of individual NPs subject to local variations and thereof, time is an important parameter. In order to prove this in [ 35 ], we measured citrate-capped Au and AgNPs diluted with ultrapure water (1/4) of different sizes at different times after their dilution (up to 72 h). Fractograms showed that there was a decrease in the absorbance signal with time due to dissolution of NPs, and that decrease depended on the type of NP and its size, being lower for Au and for 20 nm core size for both types of NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes depend on the kinetics of individual NPs subject to local variations and thereof, time is an important parameter. In order to prove this in [ 35 ], we measured citrate-capped Au and AgNPs diluted with ultrapure water (1/4) of different sizes at different times after their dilution (up to 72 h). Fractograms showed that there was a decrease in the absorbance signal with time due to dissolution of NPs, and that decrease depended on the type of NP and its size, being lower for Au and for 20 nm core size for both types of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Phenomena such as dissolution and/or passivation can be considered as a consequence of prolonged exposure to atmospheric conditions of the batch dispersion M1 [35,[38][39][40][41]. So that a part of AgNPs of the dispersion can be dissolved and released into the environment as Ag + , or it can be oxidized, generating an Ag 2 O surface film, which was indicated in other works by means of a bathochromic shift of the plasmonic band, as well as a broadening and a lower height (see Table 2 and Figure 2c).…”
Section: Characterization Of Several Batches Of Citrate Capped Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, electrophoresis has been proposed for quantification studies on biological samples; however, size distribution is not defined. For this aim, asymmetrical flow field flow fractionation (AF4) has been demonstrated to be a powerful separation strategy in the characterization and/or determination of several (nano)­materials. , AF4 coupled to UV–vis and DLS detectors in series is a very useful technique for characterization of a wide range of particle dispersions allowing their separation and establishing their distribution and stability. , The AF4-UV–vis system was employed to analyze only the size of CB particles used in ink by dispersing CB powder in aqueous media containing polymeric dispersants . However, stability studies on different dispersant matrices have not been yet performed for CB.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 AF4 coupled to UV−vis and DLS detectors in series is a very useful technique for characterization of a wide range of particle dispersions allowing their separation and establishing their distribution and stability. 36,37 The AF4-UV−vis system was employed to analyze only the size of CB particles used in ink by dispersing CB powder in aqueous media containing polymeric dispersants. 38 However, stability studies on different dispersant matrices have not been yet performed for CB.…”
Section: ■ Introductionmentioning
confidence: 99%